The nature and the image of princely power in Kievan Rus', 980-1054 : a study of sources - Hanak, Walter K., 1929- (East Central and Eastern Europe in the Middle Ages, 450-1450,, 2014)
In The Nature and the Image of Princely Power in Kievan Rus', 980-1054 , Walter K. Hanak offers a critical analysis of the annalistic, literary, and other works that provide rich if conflicting and contradictory information on the nature of princely power and their image or literary representations. The primary sources demonstrate an interaction between the reality and the notions concerning princely power and how this power generates an image of itself. The author also analyses the textual incongruities that appear to be a reflection of a number of currents -- Byzantine, Varangian, Khazar, and Eastern Slavic. The secondary sources provide a variety of interpretations, which Hanak seeks to uphold and dispute. His stress, however, is to view this evidence in the light of a newly Christianized state and the launching of a maturative process in its early history.